Natural and Cultural Education Opportunities in Protected Areas in Poland - Pisarska, Barbara (Turyzm/Tourism, 2006)
Pointing out the large scale of tourism in protected areas In Poland, and the related dangers and necessary responses, the author presents the theoretical assumptions and facts concerning natural and cultural education within their borders and in neighbouring areas.